2012
DOI: 10.1128/jb.00324-12
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ykrL ( htpX ) by Rok and YkrK, a Novel Type of Regulator in Bacillus subtilis

Abstract: Expression of ykrL of Bacillus subtilis , encoding a close homologue of the Escherichia coli membrane protein quality control protease HtpX, was shown to be upregulated under membrane protein overproduction stress. Using DNA affinity chromatography, two proteins were found to bind to the promoter region of ykrL : Rok, known as a repressor of competence and genes for extracytoplasmic functions, and YkrK, a novel type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 40 publications
0
9
3
Order By: Relevance
“…6B of reference 17). Since one of the three proposed YkrK binding sites happened to overlap the Ϫ35 box of the ykrK A promoter, they predicted that ykrK expression might be subject to autoregulation (17). However, we found in this study that disruption of the ykrK gene had no effect on expression of ykrK-bgaB ( Fig.…”
Section: Resultscontrasting
confidence: 54%
See 4 more Smart Citations
“…6B of reference 17). Since one of the three proposed YkrK binding sites happened to overlap the Ϫ35 box of the ykrK A promoter, they predicted that ykrK expression might be subject to autoregulation (17). However, we found in this study that disruption of the ykrK gene had no effect on expression of ykrK-bgaB ( Fig.…”
Section: Resultscontrasting
confidence: 54%
“…A recent report by Marciniak et al showed that expression of the B. subtilis htpX gene was under dual negative control by the Rok repressor and YkrK, a novel type of transcriptional regulator (17). However, we have found that some of the propositions and predictions in the report by Marciniak et al (17) were controversial. In the present study, we have identified the authentic promoters of htpX and ykrK, redefined the YkrK operator, and recharacterized transcriptional regulation of htpX and ykrK.…”
contrasting
confidence: 47%
See 3 more Smart Citations